ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM LAGU ANAK SEBAGAI BAHAN AJAR DI KELAS 1 SEKOLAH DASAR - Rusti Ekasari; Muhammad Juliyansyah Putra; Sunedi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study describes the values of character education in the children's song Kasih Ibu dan Sayang Lagi as teaching materials in elementary school grades. This study uses descriptive qualitative methods and data collection techniques used in this study are observation, interviews and documentation. The informants in this study were class I teachers and class I students at SD Negeri 88 Palembang. The results of this study indicate that students' understanding of character values in children's songs is quite good. The inhibiting factors are caused by several factors, differences in the character of each student, differences in the understanding abilities of students and students who are classified as passive. The positive impact that arises after learning the values of character education is that in addition to students knowing and memorizing the children's song entitled Love, Mother and Dear All, students also understand and understand the character values contained in the children's song. Meanwhile, the negative impact that arises after learning is that some students only just memorize the song but don't know the value of the character in the song. Keywords: Character Education, Children's Songs, Teaching Materials.